An Innovative Security and Privacy Algorithm for AWS Cloud Computing - Aditya Gedam,; Jeetendra Singh Yadav, (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Cloud computing has revolutionized data storage and processing, with Amazon Web Services (AWS) emerging as a leading provider. However, ensuring robust security and privacy remains a critical challenge due to the increasing complexity and sophistication of cyber threats. This paper proposes an innovative security and privacy algorithm specifically designed for AWS cloud computing environments. The proposed algorithm integrates dynamic data encryption using AES and RSA, a real-time intrusion detection system powered by machine learning, and a hybrid Role-Based and Attribute-Based Access Control (RBAC & ABAC) model. Additionally, privacy-preserving data sharing using homomorphic encryption and a secure key management system leveraging AWS Key Management Service (KMS) are implemented to safeguard sensitive data. The algorithm emphasizes performance optimization to minimize latency and computational overhead. Comprehensive evaluation on real-world datasets will assess metrics such as encryption/decryption time, response time, scalability, and resistance to attacks. The results aim to deliver a scalable, efficient, and reliable security framework, addressing current vulnerabilities and enhancing trust in AWS cloud services.
Keywords: AWS Cloud Computing; Security Algorithm; Privacy Protection; Data Encryption; Intrusion Detection System (IDS); Role-Based Access Control (RBAC)